Pengaruh Pemberian Dexmedetomidine Pada General Anestesi Terhadap Stabilitas Nadi Durante Operasi Open Reduction and Internal Fixation (ORIF) - Oivhianti Pagala; Hafizh Difa Salsabil; Reyhan Micho Atallah; Mukti Sejati; Yusrina; Maulina Galuh Arifah; Rio Kristian Nugroho (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Open Reduction and Internal Fixation (ORIF) is a surgical procedure commonly performed to treat fractures by restoring anatomical bone alignment and stabilizing bone fragments using internal fixation devices. During surgical procedures performed under general anesthesia, maintaining hemodynamic stability is essential to ensure patient safety and optimal surgical outcomes. Heart rate is one of the important indicators used to assess the hemodynamic condition of patients during surgery. Dexmedetomidine is a selective α2-adrenergic agonist widely used as an anesthetic adjuvant because of its sedative, analgesic, and sympatholytic properties that can suppress sympathetic responses and maintain cardiovascular stability during surgery. Objective: To determine the effect of dexmedetomidine administration during general anesthesia on heart rate stability during ORIF surgery at RSUD Ibu Fatmawati Soekarno Surakarta. Methods: This study used a descriptive observational approach conducted in the operating room of RSUD Ibu Fatmawati Soekarno Surakarta. The research sample consisted of five patients undergoing ORIF surgery under general anesthesia with dexmedetomidine administration. Data were collected through intraoperative monitoring of heart rate using standard anesthesia monitoring equipment. Results: The results showed that intraoperative heart rate ranged between 53–62 beats per minute, indicating relatively stable hemodynamic conditions during surgery. Conclusion: The administration of dexmedetomidine during general anesthesia may help maintain heart rate stability during ORIF surgery.